Self-SealTM Reagent: Evaporation Control for Molecular Histology Procedures without Chambers, Clips or Fingernail Polish. (August 1997) - Sullivan, Daniel E.; Bobroski, Lisa E.; Bagasra, Omar; Finney, Michael
Sensitive nucleic acid based detection methods such as in situ PCR, in situ RT-PCR and PRINS have great potential in the areas of developmental biology, pathogenesis and diagnostics. However, control of evaporation from in situ reactions is critical to ensure reliable data. Self-Seal TM Reagent, a component added directly to the in situ reaction mixture, effectively controls evaporation during in situ procedures by creating an evaporation-limiting barrier around the periphery of a standard cover glass as the reaction proceeds. At the end of the procedure, the cover glass is easily removed by soaking in an aqueous solution. A model is presented for how Self-Seal Reagent controls evaporation while maintaining reagent concentrations. Self-Seal Reagent is shown to be effective in the detection of HIV sequences in cells by in situ PCR.